Pemanfaatan MATLAB dalam Analisis Turunan Parsial : Visualisasi dan Implementasi Fungsi Multivariat - Nazwa Pahira Dongoran; Asri Cahyati Sitorus Pane; Syabila Amalia Wardani (Jurnal Pengabdian Masyarakat Sains dan Teknologi, 2024)
Turunan parsial is one of the fundamental concepts in multivariate calculus that has many applications, such as optimization, data analysis, and mathematical modeling. Understanding theory is often difficult, especially when there is no visual aid. This article discusses the use of MATLAB as a powerful tool for parsial analysis and visualization. Through the use of 3D charting and symbolic computing features, MATLAB facilitates multivariate function analysis. Research on the function f(x,y)=x^2+y^2+xy shows how parsial turunan is observed and visualized in an interactive manner. This article's goal is to encourage the use of MATLAB in long-term math education and research.